C−H Arylation of Thiophenes with Aryl Bromides by a Parts-per-Million Loading of a Palladium NNC-Pincer Complex - Purta, Anggi Eka; Ichii, Shun; Tazawa, Aya; Uozumi, Yasuhiro (Synlett, 2020)
A palladium NNC-pincer complex efficiently catalyzed the direct arylation of thiophene derivatives with extremely low palladium loadings of the order of parts per million. Thus, the reaction of various thiophenes with aryl bromides in the presence of 25–100 mol ppm of chlorido[(2-phenyl-κ-C2)-9-phenyl-1,10-phenanthroline-κ2-N,N′]palladium(II) NNC-pincer complex, K2CO3, and pivalic acid in N,N-dimethylacetamide afforded the corresponding 2- or 5-arylated thiophenes in good to excellent yields. A combination of the present C–H arylation and Hiyama coupling with the same NNC-pincer complex provides an efficient synthesis of unsymmetrical 2,5-thiophenes with catalyst loadings at mol ppm levels.
Keywords: C–H functionalization; arylation; palladium catalysis; pincer complexes; thiophenes; Hiyama coupling